2019
DOI: 10.1093/hmg/ddz058
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1 regulates extracellular matrix-cell interactions in the second heart field

Abstract: Tbx1, the major candidate gene for DiGeorge or 22q11.2 deletion syndrome, is required for efficient incorporation of cardiac progenitors of the second heart field (SHF) into the heart. However, the mechanisms by which TBX1 regulates this process are still unclear. Here, we have used two independent models, mouse embryos and cultured cells, to define the role of TBX1 in establishing morphological and dynamic characteristics of SHF in the mouse. We found that loss of TBX1 impairs extracellular matrix (ECM)-integ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 60 publications
6
23
0
Order By: Relevance
“…and "basal cell carcinoma" categories in the mESC model is also consistent with recent findings in the mouse (Alfano et al, 2019;Caprio et al, 2020).…”
Section: Transcriptional Profilingsupporting
confidence: 90%
See 1 more Smart Citation
“…and "basal cell carcinoma" categories in the mESC model is also consistent with recent findings in the mouse (Alfano et al, 2019;Caprio et al, 2020).…”
Section: Transcriptional Profilingsupporting
confidence: 90%
“…In both cases, DEGs were enriched in genes involved in developmental processes, as expected; in both cases, the focal adhesion KEGG pathway was significantly enriched. The latter has been validated recently in different cultured cells and in mouse mutants (Alfano et al, 2019). However, in general, GO enrichment was more dispersed in P19Cl6 cells compared to differentiated mES cells, where there was higher enrichment of specific GO terms, perhaps reflecting a more differentiated state and/or a more homogeneous cell population.…”
Section: Discussionmentioning
confidence: 64%
“…In turn, TBX1 is necessary to maintain high levels of Dvl2 expression, an important player in the transduction of WNT signaling, canonical and noncanonical, including the planar cell polarity pathway. Indeed, loss of TBX1 was associated with reduced ability to migrate in an in vitro assay, suggesting that this transcription factor may affect cytoskeletal rearrangements as previously shown in other systems [17]. Previous work in another type of skin tumors in mice, squamous cell carcinoma (SCC), has shown that TBX1 is not expressed in these tumors and it was suggested that it might have tumor suppressor activity [24].…”
Section: Discussionmentioning
confidence: 66%
“…We have previously shown that, in a different context, Tbx1 interacts with the noncanonical Wnt signaling [9] and it affects cytoskeletal organization and cell movement [17]. To determine whether TBX1 affects cell migration in BCC cells we performed a scratch-wound-healing assay with G2N2C cells and monitored their response by time-lapse microscopy for 96 h. We found that TBX1 depletion substantially reduced G2N2C cell migration into the wound area ( Figure 5).…”
Section: Tbx1 Is Important For Migration Of G2n2c Cellsmentioning
confidence: 86%
“…It is also noteworthy that Tbx1 deficiency causes DE in mTOR signaling pathway, VEGF signaling pathway, phosphatidylinositol signaling pathway and focal adhesion (Fulcoli et al, 2016), which we have also identified as Crk/Crkl-shared pathways in this study (Fig 3A and C). In fact, Tbx1 knockdown results in a reduced number/size of focal adhesions in C2C12 cells (Alfano et al, 2019), in similar ways to Crk/Crkl-deficient MEFs, we analyzed in this study (Fig 7). Taken together, Crk, Crkl, and Tbx1 may regulate the gene regulatory network by modulating global epigenetic landscape, which directly or indirectly control cell behavior through cell-matrix adhesion and metabolism.…”
Section: Discussionmentioning
confidence: 78%